Between Tafsīr and Fiqh Lineage: Ibn Kathīr’s Isolated Reading of Qs. al-Najm [53]: 39 and the Challenge to Micro-Genealogical Qur’anic Exegesis - Rifqi Favian (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2025)
In the discourse of rewarding the dead by reading the Qur’an on Qs. al-Najm [53]: 39, Ibn Kathīr is aloof from previous interpretations of the Qur’an in his argument. This study aims to trace the genealogy of the discourse of the rewarding of reading the Qur’an in tafsīr and why Ibn Kathīr became an interpreter who was alone in his argument. By tracing through genealogical reading and looking at social-historical aspects, this paper concludes that Ibn Kathīr built his argument by relying on his fiqh lineage through his teacher Ibn Firkah rather than the tafsīr lineage. Further, there is also strong evidence suggesting that this issue was actively debated, and Ibn Kathīr wanted to get involved. This paper also provides remark to Walid Saleh’s idea on genealogical tafsīr, which should also be read at the micro level, where tafsīr can be separated in the tradition of previous tafsīr. This research also emphasizes Younus Mirza’s argument that Ibn Kathīr has to be seen as a disciple of the al-Shāfi‘ī jurist rather than Ibn Taymīya.